Articulatory Feedback Deficit in Dyslexia - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1996)
An efferent or "motor-articulatory feedback" hypothesis for developmental dyslexia-phonological type is proposed from the Departments of Neurology and Psychiatry, University of Florida College of Medicine, Gainesville, FL.